Phytochemical and antimicrobial evaluation of selected medicinal plants in Meru community of Kenya - Jackson K. Mutembei; Patrick G. Kareru; Edwin S. Madivoli; Martin K. Murigi; Joseph Karanja; Kipyegon Cheruiyot; Sylvester O. Rechab; Ernest G. Maina (AOSIS, 2018)
Background: Increased resistance against antimicrobial medication used to combat bacterial infection necessitates the need for alternative medication.   Objective: This study seeks to evaluate the antimicrobial potential and phytochemical profiles of 10 medicinal plants collected from Chuka, Tharaka-Nithi County of Kenya. Plant samples were collected, dried, pulverised into fine powders and extracted with distilled water.   Methodology: Qualitative phytochemical screening and disc-agar diffusion methods were used according to standard method to determine phytochemical profile and antimicrobial activity of the aqueous extracts against four bacterial strains and a fungus.   Results: Phytochemical investigation revealed the presence of terpenoids, tannins and reducing sugars in all the plants except one. Saponins were found to be present in Albizia anthelmintica, Entada leptostachya, Raponae rhododendroides and Warbugia ugandensis. Steroids were present in seven plants while alkaloids were present in five. Albizia anthelmintica, E. leptostachya and W. ugandensis extracts were active against Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli and Candida albicans. Escherichia coli was the most susceptible bacteria against all the plant extracts tested, except Harrisonia abyssinica. Vernonia lasiopus and Uvariodendron anisatum were the least active extracts. Susceptibility against E. coli and C. albicans was significantly comparable to benzathine penicillin and streptomycin.   Conclusion: The type of ailments the plants are claimed to treat can be attributed to the presence of various classes of phytochemicals. In conclusion, the plants evaluated were found to be active against the microorganisms tested.